Synthesis, anti microbial screening and cytotoxic studies of some novel pyrazole analogs - K. Sony Jacob, Swastika Ganguly (Journal of Applied Pharmaceutical Science, 2016)
The objective of the study was to synthesize novel pyrazole analogs and evaluate their antimicrobial, anthelmintic and cytotoxic activity. Novel (Z)-1-(4-chlorophenyl)-2-(3,5-dimethyl-4-(substituited phenyldiazenyl)-1H-pyrazol-1-yl)ethanone derivatives were synthesized by conventional method using potassium carbonate in DMF, under reflux condition. The antibacterial study was carried out against gram positive and gram negative bacteria using ciprofloxacin and norfloxacin as standard drugs. Antifungal activity was compared against fluconazole and evaluated using Candida albicans (MTCC 227) and Aspergillus niger (NCIM 1056). Anthelmentic activity assay was carried out on Indian earthworm, Pheretima posthuma. In vitro cytotoxicity studies were also carried out using Dalton’s lymphoma ascites cells (DLA) and Ehrlich ascites carcinoma cells (EAC). Results of antibacterial study indicated that the compound 22 showed most promising activity against both Gram-positive and Gram-negative organisms. Compound 21 and 24, exhibited relatively good inhibitory profile against Gram negative organism. In case of compounds 25,27-30 exhibited equally potent antifungal activity as that of the standard drug fluconazole. Moreover, compound 21-24,26 showed excellent activity against C. albicans and A.niger. The in vitro cytotoxicity results and anthelmintic reports indicated compound 22 exhibited promising activity among the tested analogs. These newly synthesized pyrazole analogs, especially 21, 22 and 24 are better scaffolds to develop as broad spectrum chemotherapeutic agents.
Keywords: Pyrazole, anti-bacterial activity, anti-fungal activity, Dalton’s lymphoma ascites cells, Ehrlich ascites carcinoma cells.